The Relationship Between The Habits Of Using Personal Protective Equipment And Personal Hygiene And The Incidence Of Intestine Parasite Infections In Waste Workers At TPA Terjun Medan - Maria, Maria M.M Sitanggang; Steven Tandean; M. Oky Prabudi; Lambok Siahaan; Sinambela, Adelina Haryani; Panggabean, Yoan Carolina (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: Intestinal parasitic infections are quite a big problem and are still often found in society. Intestinal parasitic infections are caused by infections of intestinal protozoa and intestinal nematodes. Intestinal parasitic infections can result in a decline in an individual's health, nutrition, intelligence and productivity. Personal Protective Equipment (PPE) and good personal hygiene have an important role in reducing the transmission of parasites from soil to humans, both through eggs, larvae and adult parasites, especially for waste workers who have direct contact with infectious environments. In the city of Medan, the final disposal site used is TPA Terjun. Every day, TPA Terjun receives waste from various areas in the city of Medan. Workers are at high risk of being infected by intestinal parasites that spread through the soil. Objective: The purpose of this study is to determine the relationship between the habit of using PPE and personal hygiene with the incidence of intestinal parasite infections in waste workers at TPA Terjun Medan. Methods: This study included 121 subjects from TPA Terjun, Medan. This research used cross-sectional approach. Result: This study found that there was no correlation between the use of gloves, masks, protective clothing and protective shoes on the incidence of intestinal infections in waste workers at TPA Terjun Medan, also between personal hygiene and the incidence of intestinal parasite infections in waste workers at TPA Terjun Medan. Conclusion: The use of PPE is important to prevent the transmission of intestinal parasitic infections to workers at TPA Terjun, Medan.